Perioperative outcomes and management in midface advancement surgery: a multicenter observational descriptive study from the Pediatric Craniofacial Collaborative Group. Issue 8 (19th June 2018) - Glover, Chris D.; Fernandez, Allison M.; Huang, Henry; Derderian, Christopher; Binstock, Wendy; Reid, Russell; Dalesio, Nicholas M.; Zhong, John; Stricker, Paul A.
Summary: Background/Aims: The evolution of Le Fort III and Monobloc procedures with utilization of distraction devices has resulted in shortened surgical times, greater facial advancements, and decreased transfusion requirements. The aim of this observational study was to utilize data from the multicenter Pediatric Craniofacial Surgery Perioperative Registry to present and compare patient characteristics and outcomes in children undergoing midface advancement with distraction osteogenesis. Methods: We queried the Pediatric Craniofacial Surgery Perioperative Registry for children undergoing midface advancement involving distractor application from June 2012 to September 2016. Data extracted included demographics, perioperative management, complications, fluid and transfusion volumes, and length of stay. The extracted patient characteristics and perioperative variables were summarized and compared. Results: The query yielded 72 cases from 11 institutions: 49 children undergoing Le Fort III and 23 undergoing Monobloc procedures. Monobloc patients were younger, weighed less, and more likely to have tracheostomies along with elevated intracranial pressure. Greater transfusion was observed in the Monobloc group for nearly all of the transfusion outcomes evaluated. Median ICU and hospital length of stay were 2 and 3 days longer, respectively, in the Monobloc group. Perioperative complications were not uncommon, occurring in 18% of patients in the Le Fort III group and 30% in the Monobloc group. Conclusion: Monobloc procedures were associated with greater transfusion and longer ICU and hospital length of stay. Perioperative complications were more prevalent in the Monobloc group.